Skull-Mimicking Phantoms With Tunable Properties for Transcranial Ultrasound Imaging - Loic Saint-Martin; Kamran Avanaki (IEEE Access)
Non-invasive transcranial ultrasound imaging for older children and adults is constrained by acoustic effects caused by cranial bone in humans. There is very significant acoustic degradation of wave propagation through the cranium, particularly the diploe layer which is characterized by high porosity. Due to limited access to human skull samples for transcranial ultrasound imaging studies, the authors propose an epoxy resin-based skull-shaped phantom. This phantom mimic the multiple layers (inner/outer tables and the diploe region), enabling the creation of samples with realistic thickness and porosity variability. Appropriate material, replicating human bone composition, and poppy seeds, simulating diploe porosity, are incorporated. Using the data generated in this study, we developed a formula that allows inputting the desired acoustic properties of the skull to obtain the optimal material ratios for skull construction. The experimental evaluation setup involves acoustic transmission measurements and mechanical characteristic assessments. Results show that the developed phantoms exhibit comparable properties to actual human skulls. This research contributes to understanding and overcoming challenges in transcranial ultrasound imaging, paving the way for advancements in diagnostic tools by proposing accurate alternatives to human skulls for system design and development.